2015
DOI: 10.1371/journal.pone.0131448
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Support Interventions for Stroke Survivors: A Systematic Meta-Review

Abstract: BackgroundThere is considerable policy interest in promoting self-management in patients with long-term conditions, but it remains uncertain whether these interventions are effective in stroke patients.DesignSystematic meta-review of the evidence for self-management support interventions with stroke survivors to inform provision of healthcare services.MethodsWe searched MEDLINE, EMBASE, CINAHL, PsychINFO, AMED, BNI, Database of Abstracts of Reviews for Effectiveness, and Cochrane Database of Systematic Reviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 26 publications
5
110
0
3
Order By: Relevance
“…In line with other research [14,21,22], the results suggested that a group SMP may have a number of benefits such as peer support, reduced loneliness and shared problem solving. The novel aspect of a group compared to a one-to-one SMP is the addition of peer support.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with other research [14,21,22], the results suggested that a group SMP may have a number of benefits such as peer support, reduced loneliness and shared problem solving. The novel aspect of a group compared to a one-to-one SMP is the addition of peer support.…”
Section: Discussionsupporting
confidence: 89%
“…Similar impacts have been found specifically for stroke by three recent systematic reviews [17,19,21]. Firstly, Parke et al [21] reviewed 13 studies and found high quality evidence for a reduction in dependency and death, improvement in activities of daily living and evidence that the SMPs can facilitate reintegration in the community. Secondly, Lennon et al [19] reviewed 15 studies and found significant improvements in favour of SM, including confidence in recovery, stroke specific quality of life and measures of disability.…”
Section: Introductionsupporting
confidence: 53%
“…This resonates with successful self-management interventions in other chronically disabling conditions (e.g. stroke), that focus on strategies for enabling and improving behaviours and activities of daily living rather than crisis management [16,17]. Qualitative work has highlighted how people with severe COPD struggle with (and adapt to) the change in roles imposed by their condition [18].…”
Section: Difficulty Identifying Early Exacerbationsmentioning
confidence: 90%
“…These tasks include having the confidence to deal with medical management, role management and emotional management of their conditions." 93 Self-efficacy, an individual's confidence in their ability to carry out a specific task or behavior, is a mediator in the causal pathway between acquiring self-management skills and enactment of self-management behaviors. A systematic review without meta-analysis assessed the effectiveness of self-management strategies on depression, as a secondary end point, after stroke.…”
Section: Management: Self-managementmentioning
confidence: 99%